ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris Pada Perusahaan Bidang Keuangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2014) - Biantari, Resika Inas (Jurnal Ilmiah Mahasiswa FEB, 2016)
Is the research aims to analyze the influence of audit opinion, audit quality, company size, company profitability, and company solvency on audit delay. The population of this research is all financial sector companies listed in the Indonesia Stock Exchange for the period of 2011-2014. Using a purposive sampling method, the number of 64 companies is selected as samples for each year of observation, hence there 256 observations during the observation period. The data are analyzed using the descriptive statistics and the multiple linier regression analysis. The result from the descriptive statistics analysis shows that the average of audit delay is -22.37 days.The simultaneous and partial test results show that the four independent variables affect audit delay.Keywords: audit delay, timeliness financial reporting, audit opinion, audit quality, company size, profitability, solvency